THE INFLUENCE OF FINANCIAL MANAGEMENT BEHAVIOR ON THE FINANCIAL WELL-BEING OF AID RECIPENTSHOPE FAMILY PROGRAM IN PALETEANG, PINRANG DISTRICT - Hakim, Fitriani; Razak, Darmianti; Purnamasari, Rini (Islamic Financial And Accounting Review, 2024)
This Research aims to assess the relationship between Financial Management Behavior and Financial Well-Being of recipients of the Family Hope Program assistance in Paleteang District, Pinrang Regency, as well as examining the influence of Financial Management Behavior and Financial Well-Being of recipients of the Family Hope Program assistance in the same area. Financial Management Behavior includes financial management, financial planning, debt management, and the ability to save. The research method used is quantitative with an associative approach using data collection techniques, namely primary data in the form of questionnaires which are tested using descriptive analysis tests, data quality tests, classical assumption tests, hypothesis tests and simple regression analysis. The results of this research showthat Financial Management Behavior has a positive and significant relationship with the Financial Well-Being of recipients of the Family Hope Program assistance in Paleteang District, Pinrang Regency, as evidenced by the Pearson correlation value of 0.564, meaning that the two variables have a moderate correlation with a positive relationship. Financial Management Behavior influences Financial Well-Being, this is proven by the calculated t value > t table or 6.694 > 1.985 with a significance of 0.00 < 0.05.